PELAKSANAAN PERJANJIAN SEWA BELI KIOS DI PASAR KALINYAMATAN KABUPATEN JEPARA - Dwi Nggoni Saputra, Suradi, Bambang Eko Turisno (Diponegoro Law Journal, 2012)
Kalinyamatan market is one of the traditional market in the city of Jepara. In the call market Kalinyamatan because the market is located in the district Kalinyamatan. Market relocated and renovated in 2001 after the old building markets and less orderly rundown. This market provides to the kiosk or shop that will buy stall or shop, the local government gave the city of Jepara policies to those who want to buy at the market stall or shop Kalinyamatan not with the system but with the sale and purchase agreement hire purchase system. The research method is empirical juridical approach. Specifications of this study conducted a descriptive analysis. Data collection techniques using primary data through interviews and guided independent secondary data obtained through library materials. Analytical methods of data using qualitative methods. The results showed that the implementation of the kiosk lease hire purchase must go through a binding agreement between the two parties and there are procedures in the agreement and agreements governing. If there is a breach in the agreement then the market will do the warning between the parties in accordance with the initial agreement agreed to by both parties between the market and the buyers that when the stall rental period of 3 months in a row did not have to pay installments in accordance agreed the kiosk will be taken over again by the market, in accordance with the provisions governing the initial agreement.